Precision Molecular Pathology of Myeloid Neoplasms (Molecular Pathology Library,, 2018)
This volume provides a comprehensive, state-of-the art review of myeloid neoplasms. The book presents updated information on epidemiology, clinical presentation, morphologic findings, molecular genomic abnormalities, pathogenesis, and target therapies. The text helps to guide accurate diagnosis, the administration of appropriate ancillary molecular tests, patient management, and investigative efforts. Written by experts in the field, Precision Molecular Pathology of Myeloid Neoplasms serves as a valuable resource for pathologists, hematologists/oncologists, fellows, and researchers in understanding the molecular pathology of myeloid neoplasms. .